Media hegemony in Wikipedia articles on Chilean politics - Toro Fernández, Carla; Díaz Rubio, Patricia; Collipal Martínez, Michelle (Re-presentaciones: Periodismo, comunicación y sociedad, 2025)
This study analyzes the use of references in Wikipedia articles about politics in Chile (2020-2025), in order to identify possible patterns of media concentration in cited sources. Relying on quantitative methodological procedures, the five most cited media sources were collected from a total of 100 intentionally selected articles. The results show a predominance of traditional media (73%), particularly La Tercera, Biobío Chile, Emol, and Cooperativa, while only 20% correspond to alternative or independent media, and 7% to official sources. This concentration is further evidence of the cultural hegemony of media holdings in the Chilean context, this time visible also in digital encyclopedic content.
Keywords: Wikipedia; Hegemonic media; Media plurality; Media hegemony; Informational ecosystem